Analisis Data Turbin Angin Bilah Taper di Pantai Payangan, Sumberejo, Kec. Ambulu, Jember - Muhammad Eka Rizky; Muhamad Auriel Langit R; Naka Sabda Pratama; Andi Bagus Prasetyo; Juliawan Tri Andika P; Bintang Marchegianno R; Mico Syah Putra; Firdaus Afiyata M; Sena Adi S; Dito Pramudya N; Asbi Solihin; Thoriqur Rahman; Angga Maufirotus (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The largest source of energy currently utilized is still predominantly from fossils. Fossil energy sources are non-renewable so over time they will run out. So it is necessary to utilize renewable energy sources. One renewable energy source that is environmentally friendly and easy to obtain is wind energy. Wind is a collection of air that is experiencing movement due to a difference in pressure on the earth's surface. Wind will move from areas of high pressure to areas of lower pressure. Experimental research on wind energy is a useful energy that can be put to good use. Wind energy is a form of energy that comes from utilizing air flow in the atmosphere to produce mechanical or electrical energy. The main technology used to utilize wind energy is a wind turbine, which converts wind kinetic energy into electrical energy through a generator. Which of course also requires sufficient wind speed so that the wind turbine can rotate and produce mechanical movement in the form of rotational torque which can then be converted into electrical energy. Wind energy has great potential as a clean, sustainable and environmentally friendly resource, as it does not produce greenhouse gas emissions or hazardous waste during its operation. However, wind energy development faces challenges such as fluctuations in wind speed, large land requirements, visual impacts, and potential disruption to local ecosystems. With technological innovation and careful planning, wind energy can be a significant solution to meet global energy needs in a sustainable manner.